ANALISIS KEPUTUSAN PEMBELIAN DI TOKOPEDIA YANG DIPENGARUHI CELEBRITY ENDORSER, BRAND IMAGE, KELOMPOK REFERENSI DAN USIA - Sembiring, Carolina F.; Priskila, Enia Karina; Mangani, Ktut Silvanita (Fundamental Management Journal, 2016)
With higher dynamics of lifr makes people want everything quick and instant. It resulted with companies now starting to do e-commerce. The purpose of this research are to find out (1) celebrity endorser influence on purchasing decision in Tokopedia (2) brand image influence on purchasing decision in Tokopedia (3) reference group influence on purchasing decision in Tokopedia (4) age influence on purchasing decision in Tokopedia (5) celebrity endorser, brand image, reference group and age influences on purchasing decision in Tokopedia. Data were analyzed using Logistic Regression. The results of this research are (1) there is no significance influence between celebrity endorser and purchasing decision in Tokopedia. This is indicated by significant value 0.588 greater than 0.05 (2) ) there is significance influence between brand image and purchasing decision in Tokopedia. This is indicated by significant value 0.003 smaller than 0.05 (3) there is significance influence between reference group and purchasing decision in Tokopedia. This is indicated by significant value 0.000 smaller than 0.05 (4) there is no significance influence between age and purchasing decision in Tokopedia. This is indicated by significant value 0.186 greater than 0.05 (5) celebrity endorser, brand image, reference group and age together affect on purchasing decision in Tokopedia of 71.2%